2018
DOI: 10.5194/cp-14-2053-2018
|View full text |Cite
|
Sign up to set email alerts
|

What climate signal is contained in decadal- to centennial-scale isotope variations from Antarctic ice cores?

Abstract: Abstract. Ice-core-based records of isotopic composition are a proxy for past temperatures and can thus provide information on polar climate variability over a large range of timescales. However, individual isotope records are affected by a multitude of processes that may mask the true temperature variability. The relative magnitude of climate and non-climate contributions is expected to vary as a function of timescale, and thus it is crucial to determine those temporal scales on which the actual signal domina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 60 publications
3
56
2
Order By: Relevance
“…In summary, the signal-to-noise ratios of accumulation rates at UG are consistent with those determined by Schlosser et al (2014) and Altnau et al (2015) for firn cores from Fimbul Ice Shelf, DML, and much higher than those found in low-accumulation areas of the Amundsenisen mountain range, DML Altnau et al, 2015). Generally, the higher the accumulation rates at a specific site are, the higher the signal-to-noise ratios for stable water isotopes and accumulation rates are (Hoshina et al, 2014;Münch et al, 2016). Hence, the UG region with higher accumulation rates as compared to low-accumulation sites on the EAIS (e.g.…”
Section: Potential Noises Influencing Ug Firn Core Recordssupporting
confidence: 82%
“…In summary, the signal-to-noise ratios of accumulation rates at UG are consistent with those determined by Schlosser et al (2014) and Altnau et al (2015) for firn cores from Fimbul Ice Shelf, DML, and much higher than those found in low-accumulation areas of the Amundsenisen mountain range, DML Altnau et al, 2015). Generally, the higher the accumulation rates at a specific site are, the higher the signal-to-noise ratios for stable water isotopes and accumulation rates are (Hoshina et al, 2014;Münch et al, 2016). Hence, the UG region with higher accumulation rates as compared to low-accumulation sites on the EAIS (e.g.…”
Section: Potential Noises Influencing Ug Firn Core Recordssupporting
confidence: 82%
“…Retrieving these climate proxies from ice cores allows to reconstruct past changes in earth's climate history from annual to glacial-interglacial time scales (e.g. Brook and Buizert, 2018;Münch and Laepple, 2018). More specifically, stable water isotopes are a well-established proxy for past air temperature variations in Greenland (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It must be emphasized, however, that during the last glacial maximum and the Holocene the decrease in temperature variations as the mean temperature increased while exhibiting a zonal pattern may explain some discrepancies between the hemispheres [33,34].…”
Section: The 576-1152 Yr Bandmentioning
confidence: 99%